Utilizing Production Viable Valve Strategies at Elevated Speeds and Loads to Improve Volumetric Efficiency via Intake Valve Modulation - Vos, Kalen R.; Shaver, Gregory M.; McCarthy, James; Farrell, Lisa (Frontiers in Mechanical Engineering, 2018)
Valvetrain flexibility enables the optimization of the engine’s ability to breathe across the operating range, resulting in more efficient operation. The authors have shown the merit of improving volumetric efficiency via valvetrain flexibility to improve fuel efficiency at elevated engine speeds in previous work. This study focuses on production viable solutions targeting similar volumetric efficiency benefits via delayed intake valve closure at these elevated engine speeds. Specifically, the production viable solutions include reducing the duration at peak lift, as well as reducing the amount of hardware required to achieve a delayed intake closure timing. It is demonstrated through simulation that delayed intake valve modulation at an elevated speed (2200 RPM) and load (12.7 bar BMEP) is capable of improving volumetric efficiency via a production viable lost motion enabled boot profile shape. Phased and dwell profiles were also evaluated. These profiles were compared against each other for two separately simulated cases: 1) modulating both intake valves per cylinder, and 2) modulating one of the two intake valves per cylinder. The boot, phase, and dwell profiles demonstrate volumetric efficiency improvements of up to 3.33%, 3.41%, and 3.5% respectively for two valve modulation, while realizing 2.79%, 2.59%, and 3.01% respectively for single valve modulation. As a result, this paper demonstrates that nearly all of the volumetric efficiency benefits achieved while modulating IVC via dwell profiles are possible with production viable boot and phased profiles